Condiciones de posibilidad de los Planes de Igualdad como política de promoción de la equidad en el ámbito laboral - Ballesteros Doncel, Esmeralda (Cuadernos de Relaciones Laborales, 2010)
The Act 3/2007, for the effective equality of Women and Men establishes the gender equality plans as positive action for promoting equity in the labour markets. This study has found that the equality plans will not be able to eliminate, for yes alone, the discriminatory practices that persist on the labour markets, though they represent an opportunity to think about the organization of the human resources from a sensitive perspective with the conciliation. Our presentation also suggests to the Department of Equality makes a technical guide who orientates to the companies in the elaboration of the gender equality plans.
Keywords: Gender equality plans; Equal opportunities; Legislation; Sexual division of labour; Women